EVALUASI DAMPAK KEBIJAKAN PENANGGULANGAN PENYAKIT MASYARKAT (STUDI KASUS PADA PENGEMIS, GELANDANGAN DAN ORANG TERLANTAR DI KABUPATEN BANYUMAS) - Rizkiana Nur Fadillah; Suryoto Suryoto; Anggara Setya Saputra (Jurnal Kebijakan Pemerintahan, 2026)
This study aims to evaluate the impact of the social ill-management policy on beggars, vagrants, and abandoned people (PGOT) in Banyumas Regency, as stipulated in Banyumas Regency Regulation Number 14 of 2020. The study employed quantitative methods, with data collection techniques including questionnaires, observation, and documentation. The sample size for this study was 100 respondents, determined using a multistage random sampling technique. Data analysis was performed using the Wilcoxon Signed Ranks Test. The results indicate that the policy has had a significant impact on the individual, organizational, community, and institutional dimensions, as well as social systems and systems. The policy has been able to encourage behavioral changes in PGOT, improve organizational performance, create public order, and strengthen cross-sectoral collaboration. However, the policy's effectiveness is not evenly distributed and requires strengthening in guidance, coordination, and supervision for greater sustainability. Keywords: Banyumas Regency, PGOT, Policy.